Positive electrode slurry and preparation method and application thereof

By using a positive electrode slurry containing nitrile polymer and flexible agent in a lithium iron phosphate thick electrode, problems such as insufficient conductivity and poor adhesion are solved, the overall performance and stability of the electrode are improved, and the life of the battery is extended. Reduced production costs.

CN119495744APending Publication Date: 2025-02-21ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411509488.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In actual production, lithium iron phosphate thick electrodes face problems such as insufficient conductivity, poor adhesion, easy release of the electrode sheet and brittle breakage, which affects the overall performance and stability of the electrode.

Method used

A positive electrode slurry, including lithium iron phosphate, conductive agent and glue solution, which is prepared from nitrile polymer, flexible agent and PVDF. The flexible agent has a polyether backbone, an alkane segment and a phosphate group, through The combination of these components improves the conductivity, adhesion and compaction density of the electrode sheet.

Benefits of technology

It achieves good adhesion of the electrode sheet, improves the compaction density of the electrode sheet and the conductivity of the electrode, reduces the material breakage and peeling of the electrode sheet during charging and discharging, extends the cycle stability and life of the battery, and Reduced production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495744A_ABST
    Figure CN119495744A_ABST
Patent Text Reader

Abstract

The invention provides positive electrode slurry as well as a preparation method and application thereof. The preparation raw materials of the positive electrode slurry comprise lithium iron phosphate, a conductive agent and a glue solution, and the preparation raw materials of the glue solution comprise a butyronitrile polymer, a flexibilizer and PVDF. According to the positive electrode slurry disclosed by the invention, the binding power of a pole piece is ensured by utilizing the characteristic of high viscosity of the butyronitrile polymer, and the compaction density of the pole piece is improved by combining with the flexibilizer. The flexibilizer has a polyether main chain, the main chain has an alkane chain segment, the main chain internally contains an ester group and a phosphate group, the phosphate group can be anchored on the surface of lithium iron phosphate, the alkane chain segment contained in the flexibilizer can stretch in a solvent, and the granularity of lithium iron phosphate is dispersed through steric hindrance. The ester monomer in the butyronitrile polymer provides molecular flexibility, so that the pole piece can be prevented from being embrittled due to rolling. The invention also provides a preparation method and application of the positive electrode slurry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a positive electrode slurry and a preparation method and application thereof. Background Art

[0002] In modern energy storage technology, lithium-ion batteries are widely used in electric vehicles, portable electronic devices, and energy storage systems due to their superior energy density, long life, and low self-discharge rate. In particular, lithium iron phosphate (LiFePO4), as a new type of lithium-ion battery cathode material, has attracted widespread attention for its high safety, long cycle life, and good thermal stability. As a cathode material for lithium-ion batteries, lithium iron phosphate has many significant advantages over traditional lithium cobalt oxide (LiCoO2) or nickel cobalt manganese oxide (NCM). First, lithium iron phosphate has higher thermal and chemical stability, reducing the risk of overcharging and short circuit, thereby improving battery safety. Secondly, its long cycle life allows the battery to maintain a high capacity during long-term use, significantly reducing the frequency of battery replacement and reducing long-term use costs. In addition, the environmental friendliness and relatively low cost of lithium iron phosphate have also led to its active promotion in the field of green energy.

[0003] An important feature of lithium iron phosphate batteries is the use of thick electrodes, which helps to improve the energy density and power output of the battery. In lithium-ion batteries, the application of thick electrodes can significantly improve the energy density and power density of the battery. Thick electrode materials in the positive or negative electrode of the battery can increase the energy storage capacity of the battery by increasing the thickness of the electrode. However, the manufacturing process of thick electrodes is complicated, involving multiple links such as coating, drying, and pressing, which have an important impact on the performance of the final electrode. Effective electrode coating technology is the key to ensuring battery performance and manufacturing stability. The coating of electrode materials is one of the key steps in the preparation of batteries. The electrode coating process usually includes the following steps: preparing slurry, coating, drying and compacting. The coating of lithium iron phosphate thick electrodes requires special attention to the slurry formulation, coating thickness and uniformity. The slurry formulation usually includes lithium iron phosphate powder, conductive agent (such as carbon black or conductive polymer) and binder (such as polyvinylidene fluoride PVDF). The ratio and formulation of these components directly affect the conductivity, mechanical strength and adhesion of the electrode.

[0004] In the preparation of thick electrodes, the conductivity and adhesion of electrode materials are two important performance indicators. The conductivity directly affects the overall conductivity of the electrode, which in turn affects the power output of the battery. Adhesion affects the stability and life of the electrode material. If the adhesion is insufficient, the electrode material may have problems such as demolding, powdering and brittle fracture. Although lithium iron phosphate thick electrodes have significant advantages in improving battery performance, they still face many challenges in actual production. In particular, several key problems in the coating process, such as poor conductivity of the pole piece, poor adhesion, easy demolding and powdering of the pole piece, and brittle fracture, seriously affect the overall performance and stability of the electrode. Among them, conductivity is one of the core factors that determine the performance of the electrode. Although lithium iron phosphate has a high theoretical capacity, due to its poor conductivity, it needs to be improved by adding a conductive agent. However, the distribution and amount control of the conductive agent in the thick electrode is still a major challenge. If the conductive agent is unevenly distributed or insufficiently used, it may lead to a poor current conduction path inside the electrode, thereby reducing the overall conductivity of the electrode and the power output of the battery. The role of the binder is to firmly adhere the electrode material to the current collector. However, during the preparation of thick electrodes, the performance and amount of the binder must be strictly controlled. If the binder is not selected or proportioned properly, it may lead to demolding, powdering or even brittle fracture of the electrode material. Poor adhesion not only affects the mechanical strength of the electrode, but may also lead to poor contact between the electrode and the electrolyte, thereby affecting the overall performance of the battery. In the production process of thick electrodes, the demolding and powdering problems of the pole piece are particularly prominent. The electrode material may have uneven thickness and insufficient adhesion during the coating and drying process. This situation will cause the pole piece to demold and powder during subsequent processing, which will affect the life and stability of the battery. Brittle fracture refers to the phenomenon that the electrode material breaks due to mechanical stress or environmental factors during use. For thick electrodes, the brittle fracture problem of the material is particularly serious, which is usually closely related to factors such as the structural design of the electrode, the formulation of the material, and the processing technology.

[0005] At present, thick lithium iron phosphate electrodes have significant advantages in improving the performance of lithium-ion batteries, but in practical applications, the electrode coating process still needs to be further improved, especially the insufficient conductivity and poor adhesion of the electrodes, and the easy demolding and brittle fracture of the pole pieces. In-depth exploration is still needed to improve the electrode material formula, optimize the coating process, and improve the mechanical properties of the electrodes to promote the further development and application of thick lithium iron phosphate electrode technology. Summary of the invention

[0006] The present invention aims to solve at least one of the above technical problems existing in the prior art. To this end, the present invention provides a positive electrode slurry, which has good conductivity and strong bonding force when prepared as a positive electrode, and the electrode piece is not easy to be demolded and powdered or brittle.

[0007] The invention also provides a method for preparing positive electrode slurry.

[0008] The invention also provides an application of the positive electrode slurry.

[0009] The first aspect of the present invention provides a positive electrode slurry, the raw materials for preparing the slurry include lithium iron phosphate, a conductive agent and a glue solution, the raw materials for preparing the glue solution include a nitrile polymer, a flexibility agent and PVDF, the flexibility agent has a polyether main chain, the main chain has an alkane segment, and the main chain contains an ester group and a phosphate group.

[0010] One of the technical solutions of the present invention regarding the positive electrode slurry has at least the following beneficial effects:

[0011] The positive electrode slurry of the present invention utilizes the high viscosity of the nitrile polymer to ensure the bonding force of the pole piece, and combines with the flexibilizer to improve the compaction density of the pole piece. The phosphate group of the flexibilizer can be anchored on the surface of the lithium iron phosphate, and the alkane chain segments contained in the flexibilizer can be stretched in the solvent, dispersing the particle size of the lithium iron phosphate through steric hindrance. The ester monomer in the nitrile polymer provides molecular flexibility, which can prevent the pole piece from becoming brittle due to rolling.

[0012] In addition, the positive electrode slurry of the present invention, due to the combined use of nitrile polymer and flexibilizer, can effectively reduce the material rupture and peeling caused by volume change of the pole piece during the charge and discharge process, thereby improving the cycle stability and life of the battery. The combination of flexibilizer and nitrile polymer can form a more uniform structure in the pole piece, reduce stress concentration, and thus reduce the safety risk caused by thermal runaway or mechanical damage. Since the flexibilizer and nitrile polymer can maintain their physical properties at higher temperatures, the positive electrode slurry can better maintain its mechanical stability and electrochemical performance under high temperature environment. By optimizing the compaction density of the pole piece and the dispersibility of the electrode material, the volume utilization rate of the electrode can be improved, thereby improving the energy density of the battery. Further, the combination of nitrile polymer and flexibilizer can reduce the dependence on other high-cost materials in the production process of the pole piece, thereby reducing the overall production cost. Due to the addition of flexibilizer and nitrile polymer, the fluidity and film-forming properties of the slurry are improved, making it easier to operate and control during the production process, thereby improving production efficiency. As a result, the positive electrode slurry is ultimately more competitive in practical applications, improving the comprehensive performance and economic benefits of the battery.

[0013] According to some embodiments of the present invention, the conductive agent is a mixture of a first conductive agent, a second conductive agent and a third conductive agent, the first conductive agent includes carbon black, the second conductive agent includes at least one of carbon nanotubes and carbon fibers, and the third conductive agent includes graphene nanosheets.

[0014] According to some embodiments of the present invention, in the first conductive agent, the carbon black includes SP (super p li, abbreviated as SP), and the super dense high conductive carbon black SP is a pure black fine particle or powder, insoluble in water, acid and alkali, and can burn in the air. Due to its strong conductive properties, it is widely used as a conductive additive for lithium ion batteries. Carbon black with high porosity can form a network structure of carbon black at a very low addition amount, and give the product excellent conductive properties.

[0015] According to some embodiments of the present invention, the carbon nanotubes (Carbon Nanotubes, CNTs) of the second conductive agent are a hollow tubular structure formed by a single layer of carbon atoms arranged in a hexagonal grid. They can be single-layer (single-walled carbon nanotubes, SWCNT) or multi-layer (multi-walled carbon nanotubes, MWCNT). CNTs have extremely high strength and rigidity, excellent electrical conductivity and thermal conductivity. In addition, they also have a high specific surface area and are suitable for various electronic, material and energy applications. Among them, SWCNT is a carbon nanotube consisting of only one layer of carbon atoms, and the diameter is usually between 1-2 nanometers. SWCNTs have excellent electrical, mechanical and thermal properties, especially excellent performance in electrical conductivity and mechanical strength. Their electrical properties can vary due to their structure (conductor or semiconductor), which is suitable for fields such as nanoelectronics and molecular sensors. The carbon fiber of the second conductive agent includes vapor grown carbon fiber (Vapor Grown Carbon Fiber, VGCF), which is a carbon fiber prepared by vapor deposition, with a specific structure and performance, which is different from traditional carbon fibers and carbon nanotubes.

[0016] According to some embodiments of the present invention, the third conductive agent is flake graphite, and the grades include KS-6.

[0017] According to some embodiments of the present invention, the mass ratio of the first conductive agent, the second conductive agent and the third conductive agent is 1:0.3-0.8:0.4-0.7.

[0018] According to some embodiments of the present invention, the amount of the lithium iron phosphate added to the positive electrode slurry is 92% to 96% by mass.

[0019] According to some embodiments of the present invention, the conductive agent is added to the positive electrode slurry in an amount of 0.8% to 2.2% by mass.

[0020] According to some embodiments of the present invention, the amount of the glue added to the positive electrode slurry is 1.0% to 1.8% by mass.

[0021] According to some embodiments of the present invention, the method for preparing the nitrile polymer comprises the following steps:

[0022] (1) introducing nitrogen into the solvent to remove oxygen, and then adding n-butyronitrile, carboxylic acid, acrylate and dodecyl methacrylate monomers;

[0023] (2) adding an initiator and heating the reaction until the solid precipitate disappears;

[0024] (3) dialyzing the product obtained in step (2) with deionized water to remove impurity ions in the solution, freezing and solidifying the product, and then freeze-drying the product in a vacuum manner to obtain the nitrile polymer.

[0025] The carboxylic acid may be formic acid, acetic acid or propionic acid.

[0026] The solvent may be acetone.

[0027] The acrylate may be methyl acrylate.

[0028] Butyronitrile, carboxylic acid, acrylate and dodecyl methacrylate monomers are low Tg monomers.

[0029] The low Tg monomer has a Tg of <-20°C and is an acrylate monomer, which may be dodecyl methacrylate, n-butyl acrylate, ethyl acrylate, n-propyl acrylate, and the like.

[0030] According to some embodiments of the present invention, the method for preparing the flexibilizer comprises the following steps:

[0031] a. Mixing ethylene glycol with sodium hydroxide to obtain a mixture, heating the mixture under a protective atmosphere, adding ethylene oxide to the mixture, and keeping the mixture warm to obtain polyoxyethylene ether glycol;

[0032] b. Add the polyoxyethylene glycol and n-propanol to a preheated reactor, add phosphorus pentoxide, keep warm for reaction, and cool with water to obtain the flexibilizer.

[0033] According to some embodiments of the present invention, the method for preparing the glue solution comprises the following steps: adding the nitrile polymer and the flexibilizer into a solvent, stirring, and then adding the PVDF to obtain the glue solution.

[0034] According to some embodiments of the present invention, the flexibilizer has a polyether main chain, the main chain has an alkane segment, and the main chain contains an ester group and a phosphoric acid group.

[0035] The phosphate groups anchor the surface of lithium iron phosphate, the alkane chain segments stretch in NMP, the steric hindrance disperses the lithium iron phosphate particles, and the ester monomers provide molecular flexibility to prevent the pole piece from becoming brittle due to rolling.

[0036] The second aspect of the present invention provides a method for preparing the positive electrode slurry of the first aspect of the present invention, comprising the following steps:

[0037] S1: adding part of the conductive agent, part of the lithium iron phosphate and part of the glue to perform first stirring and mixing;

[0038] S2: adding the remaining conductive agent and the remaining lithium iron phosphate, adding a solvent to adjust the solid content, and stirring and mixing for the second time;

[0039] S3: adding the remaining glue solution and stirring and mixing for the third time to obtain the positive electrode slurry.

[0040] A technical solution in the method for preparing positive electrode slurry of the present invention has at least the following beneficial effects:

[0041] The method for preparing the positive electrode slurry of the present invention does not require expensive equipment and complex process control, has undemanding reaction conditions, has readily available raw materials, has low production costs, and is easy to industrialize.

[0042] According to some embodiments of the present invention, the viscosity of the positive electrode slurry is 7500-10000 Pa·s.

[0043] According to some embodiments of the present invention, the solid content of the positive electrode slurry is 63% to 67%.

[0044] The third aspect of the present invention provides a lithium iron phosphate thick electrode, comprising a current collector and a coating disposed on at least one side of the current collector, wherein the coating is prepared from the positive electrode slurry of the first aspect of the present invention.

[0045] According to some embodiments of the present invention, the single-surface density of the lithium iron phosphate thick electrode is 380-400 mg / 1540.25 mm 2 .

[0046] According to some embodiments of the present invention, the single-sided surface density of the lithium iron phosphate thick electrode is 400 mg / 1540.25 mm 2 .

[0047] According to some embodiments of the present invention, the compaction density of the lithium iron phosphate thick electrode is 2.45-2.6 g / cm 3 .

[0048] A fourth aspect of the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the lithium iron phosphate thick electrode according to the third aspect of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 It is the comparative test result of the pole piece rolling transmittance of the embodiment and the comparative example. DETAILED DESCRIPTION

[0050] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.

[0051] In the first aspect, some embodiments of the present invention provide a positive electrode slurry, wherein raw materials for preparing the slurry include lithium iron phosphate, a conductive agent and a glue solution, and the raw materials for preparing the glue solution include a nitrile polymer, a flexibility agent and PVDF, wherein the flexibility agent has a polyether main chain with an alkane segment on the main chain, and contains an ester group and a phosphate group inside the main chain.

[0052] It can be understood that the positive electrode slurry of the present invention utilizes the high viscosity of the nitrile polymer to ensure the bonding force of the pole piece, and combined with the flexibilizer, the compaction density of the pole piece is improved. The phosphate group can be anchored on the surface of the lithium iron phosphate, the alkane chain segments contained in the flexibilizer can be stretched in the solvent, and the particle size of the lithium iron phosphate is dispersed through steric hindrance. The ester monomer in the nitrile polymer provides molecular flexibility, which can prevent the pole piece from becoming brittle due to rolling.

[0053] In addition, it can also be understood that the positive electrode slurry of the present invention, due to the combined use of nitrile polymer and flexibilizer, can effectively reduce the material rupture and peeling caused by volume change of the pole piece during the charge and discharge process, thereby improving the cycle stability and life of the battery. The combination of flexibilizer and nitrile polymer can form a more uniform structure in the pole piece, reduce stress concentration, and thus reduce the safety risk caused by thermal runaway or mechanical damage. Since the flexibilizer and nitrile polymer can maintain their physical properties at higher temperatures, the positive electrode slurry can better maintain its mechanical stability and electrochemical properties under high temperature environment. By optimizing the compaction density of the pole piece and the dispersibility of the electrode material, the volume utilization rate of the electrode can be improved, thereby improving the energy density of the battery. Further, the combination of nitrile polymer and flexibilizer can reduce the dependence on other high-cost materials in the production process of the pole piece, thereby reducing the overall production cost. Due to the addition of flexibilizer and nitrile polymer, the fluidity and film-forming properties of the slurry are improved, making it easier to operate and control during the production process, thereby improving production efficiency. As a result, the positive electrode slurry is ultimately more competitive in practical applications, improving the comprehensive performance and economic benefits of the battery.

[0054] In combination with the first aspect, in some embodiments of the present invention, the conductive agent is a mixture of a first conductive agent, a second conductive agent and a third conductive agent, the first conductive agent includes carbon black, the second conductive agent includes at least one of carbon nanotubes and carbon fibers, and the third conductive agent includes graphene nanosheets.

[0055] In combination with the first aspect, in some embodiments of the present invention, in the first conductive agent, the carbon black includes SP (super pli, abbreviated as SP), and the super dense high conductive carbon black SP is a pure black fine particle or powder, insoluble in water, acid and alkali, and can burn in the air. Due to its strong conductivity, it is widely used as a conductive additive for lithium-ion batteries. Carbon black with high porosity can form a network structure of carbon black at a very low addition amount, and give the product excellent conductive properties.

[0056] In combination with the first aspect, in some embodiments of the present invention, in the second conductive agent, carbon nanotubes (Carbon Nanotubes) are hollow tubular structures formed by a single layer of carbon atoms arranged in a hexagonal grid. They can be single-layer (single-walled carbon nanotubes, SWCNT) or multi-layer (multi-walled carbon nanotubes, MWCNT). CNTs have extremely high strength and rigidity, excellent electrical conductivity and thermal conductivity. In addition, they also have a high specific surface area and are suitable for various electronic, material and energy applications. Among them, SWCNT is a carbon nanotube consisting of only one layer of carbon atoms, and the diameter is usually between 1-2 nanometers. SWCNTs have excellent electrical, mechanical and thermal properties, especially excellent performance in electrical conductivity and mechanical strength. Their electrical properties can vary due to their structure (conductor or semiconductor), and are suitable for fields such as nanoelectronics and molecular sensors. Vapor-grown carbon fiber (Vapor Grown Carbon Fiber, VGCF) is a carbon fiber prepared by vapor deposition, with a specific structure and properties. It is different from traditional carbon fibers and carbon nanotubes.

[0057] In combination with the first aspect, in some embodiments of the present invention, the brand of the third conductive agent includes KS-6.

[0058] In combination with the first aspect, in some embodiments of the present invention, the mass ratio of the first conductive agent, the second conductive agent and the third conductive agent is 1:0.3-0.8:0.4-0.7.

[0059] It should be noted that, because the first conductive agent is a dot coating, the second conductive agent is a line coating, and the third conductive agent is a surface coating, the combination of the dots, lines, and surfaces can form a relatively complete coating network. Without any of them, the conductivity of the electrode will deteriorate.

[0060] In combination with the first aspect, in some embodiments of the present invention, the amount of lithium iron phosphate added to the positive electrode slurry is 92% to 96% by mass.

[0061] In combination with the first aspect, in some embodiments of the present invention, the amount of the conductive agent added to the positive electrode slurry is 0.8% to 2.2% by mass.

[0062] In combination with the first aspect, in some embodiments of the present invention, the amount of the glue added to the positive electrode slurry is 1.0% to 1.8% by mass.

[0063] In combination with the first aspect, in some embodiments of the present invention, the method for preparing the nitrile polymer comprises the following steps:

[0064] (1) introducing nitrogen into the solvent to remove oxygen, and then adding n-butyronitrile, carboxylic acid, acrylate and dodecyl methacrylate monomers;

[0065] (2) adding an initiator and heating the reaction until the solid precipitate disappears;

[0066] (3) The product obtained in step (2) is dialyzed with deionized water to remove impurity ions in the solution, and then frozen and solidified and then vacuum freeze-dried to obtain a nitrile polymer.

[0067] In step (1): n-butyronitrile, carboxylic acid, acrylate and dodecyl methacrylate monomers are low Tg monomers.

[0068] The low Tg monomer has a Tg of <-20°C and is an acrylate monomer, which may be dodecyl methacrylate, n-butyl acrylate, ethyl acrylate, n-propyl acrylate, and the like.

[0069] According to some embodiments of the present invention, the method for preparing the flexibilizer comprises the following steps:

[0070] a. Mix ethylene glycol and sodium hydroxide to obtain a mixture, heat the mixture under a protective atmosphere, add ethylene oxide, and heat the mixture to obtain polyoxyethylene ether glycol;

[0071] b. Add polyoxyethylene glycol and n-propanol to a preheated reactor, add phosphorus pentoxide, keep warm for reaction, add water to cool, and obtain a flexibilizer.

[0072] In combination with the first aspect, in some embodiments of the present invention, the method for preparing the adhesive solution includes the following steps: adding a nitrile polymer and a flexibilizer into a solvent, stirring, and then adding PVDF to obtain an adhesive solution.

[0073] In combination with the first aspect, in some embodiments of the present invention, the flexibilizer has a polyether main chain containing an ester group and a phosphoric acid group.

[0074] The phosphate groups anchor the surface of lithium iron phosphate, the alkane chain segments stretch in NMP, the steric hindrance disperses the lithium iron phosphate particles, and the ester monomers provide molecular flexibility to prevent the pole piece from becoming brittle due to rolling.

[0075] In a second aspect, in some embodiments of the present invention, there is provided a method for preparing the positive electrode slurry of the first aspect of the present invention, comprising the following steps:

[0076] S1: adding part of the conductive agent, part of the lithium iron phosphate and part of the glue solution for the first stirring and mixing;

[0077] S2: adding the remaining conductive agent and the remaining lithium iron phosphate, adding a solvent to adjust the solid content, and stirring and mixing for the second time;

[0078] S3: Add the remaining glue solution and stir and mix for the third time to obtain positive electrode slurry.

[0079] It can be understood that the method for preparing the positive electrode slurry of the present invention does not require expensive equipment and complex process control, the reaction conditions are not harsh, the raw materials are easily available, the production cost is low, and it is easy to industrialize production.

[0080] In combination with the second aspect, in some embodiments of the present invention, the viscosity of the positive electrode slurry is 7500-10000 Pa·s.

[0081] In combination with the second aspect, in some embodiments of the present invention, the solid content of the positive electrode slurry is 63% to 67%.

[0082] In a third aspect, some embodiments of the present invention provide a lithium iron phosphate thick electrode, comprising a current collector and a coating disposed on at least one side of the current collector, wherein the coating is prepared from the positive electrode slurry of the first aspect of the present invention.

[0083] It should be noted that the high viscosity of the nitrile polymer ensures good bonding between the electrode and the current collector, reducing the possibility of peeling or falling off of the electrode during use. Combined with the use of a flexibilizer, the compaction density of the electrode can be significantly increased, thereby increasing the energy density and service life of the electrode.

[0084] The alkane segments in the flexibilizer help to evenly disperse the lithium iron phosphate particles through the steric hindrance effect, avoiding the agglomeration of particles. This helps to improve the electrochemical properties of the electrode material, such as better ion and electron conduction. The ester monomers in the nitrile polymer provide molecular flexibility for the pole piece, so that the pole piece can better adapt to volume changes during rolling or charging and discharging, reducing the risk of embrittlement, thereby improving the mechanical stability and cycle life of the electrode.

[0085] Due to the good particle dispersion, the active material (lithium iron phosphate) in the electrode can participate in the electrochemical reaction more effectively, improving the battery's charge and discharge performance and energy density. Due to the good material dispersion and appropriate mechanical flexibility, the electrode can also maintain good stability under high temperature conditions, reducing the risk of thermal runaway.

[0086] It should also be noted that the use of the flexibilizer improves the mechanical toughness of the electrode, reduces structural cracking caused by stress concentration, and improves the safety of the battery during operation. Therefore, the lithium iron phosphate thick electrode prepared using the positive electrode slurry of the present invention has significant advantages in improving battery performance, improving safety and extending service life. These characteristics make it have a high application value in battery technology.

[0087] In combination with the third aspect, in some embodiments of the present invention, the single-sided surface density of the lithium iron phosphate thick electrode is 380-400 mg / 1540.25 mm 2 .

[0088] In combination with the third aspect, in some embodiments of the present invention, the compaction density of the lithium iron phosphate thick electrode is 2.45-2.6 g / cm 3 .

[0089] In a fourth aspect, in some embodiments of the present invention, a lithium-ion battery is provided, wherein the lithium-ion battery comprises the lithium iron phosphate thick electrode according to the third aspect of the present invention.

[0090] It can be understood that the lithium-ion battery of the present invention, because it includes the lithium iron phosphate thick electrode of the present invention, has all the beneficial effects of the lithium iron phosphate thick electrode.

[0091] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0092] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0093] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.

[0094] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.

[0095] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0096] Example 1

[0097] A positive electrode slurry is prepared from raw materials of lithium iron phosphate, a conductive agent and a glue solution, wherein the raw materials for preparing the glue solution are a nitrile polymer, a flexibilizer and PVDF.

[0098] First, prepare the nitrile polymer, then prepare the flexibilizer and the glue, and finally prepare the positive electrode slurry.

[0099] The specific preparation process of nitrile polymer is:

[0100] N1. First, nitrogen was introduced into the acetone solvent to deoxygenate for 2 h, and then n-butyronitrile, acetic acid, methyl acrylate, and dodecyl methacrylate monomers were added, wherein the mass ratio of n-butyronitrile, acetic acid, methyl acrylate, and dodecyl methacrylate monomers was 90:3:2:5, and stirred at 20 rpm for 30 min;

[0101] N2, add 1 mol / L potassium sulfate as an initiator, raise the temperature to 55°C, and react for 2 hours until no solid precipitates;

[0102] N3, the product obtained in step N2 is dialyzed with deionized water to remove impurity ions in the solution, and then frozen to solidify, and then placed in a freeze dryer for vacuum freeze drying to obtain a butyronitrile polymer.

[0103] The specific preparation process of the flexibilizer is:

[0104] N1: Mix ethylene glycol and sodium hydroxide in acetone solvent to obtain a mixed solution. In the mixed solution, the concentration of ethylene glycol is 2 mol / L, and the concentration of sodium hydroxide is 5 mg / mL. Heat the mixed solution to 150°C under the protection of an inert gas, then add ethylene oxide, and keep the temperature at 150-160°C for 2 hours to obtain polyoxyethylene ether glycol. The volume ratio of the mixed solution to ethylene oxide is 1.5:1.

[0105] N2: Preheat the reactor to 50°C, add polyoxyethylene ether glycol and n-propanol in a mass ratio of 4.5:1, then slowly add phosphorus pentoxide in a mass ratio of 1.2:1, and react at 120°C for 2 hours. After the reaction is completed, add water for cooling, and the amount of water added is 5 times the total mass of all the reaction raw materials to obtain the flexibilizer.

[0106] The specific preparation steps of the glue solution are:

[0107] The above-mentioned nitrile polymer and the flexibility agent are mixed in a mass ratio of 4:1 (wherein the content of the flexibility agent is calculated based on the solid content of the flexibility agent), slowly added into NMP, and stirred at 80° C. and 20 rpm for 1 hour to obtain component A.

[0108] Component A and PVDF (brand name Solvay 5130) were mixed in a mass ratio of 1:1 and added into NMP. The mixture was stirred at 200 rpm for 2 h. After mixing, a glue solution with a solid content of 8% was obtained.

[0109] Preparation of positive electrode slurry:

[0110] The raw materials are: by mass percentage, 96% lithium iron phosphate, 1.8% glue, 1.0% conductive agent a, 0.7% conductive agent b, and 0.5% conductive agent c. The conductive agents a, b, and c are SP, CNT, and KS-6, respectively.

[0111] 1. Add conductive agent b, half amount of lithium iron phosphate and half amount of glue solution, and stir at 1000rpm for 30min;

[0112] 2. Add conductive agent a, conductive agent c and the remaining lithium iron phosphate, add NMP to adjust the solid content to 80%, and stir at 2000 rpm for 100 minutes;

[0113] 3. Add the remaining glue solution and stir at 1000 rpm for 60 min to obtain a positive electrode slurry with a viscosity of 8200 Pa·s and a solid content of 66%.

[0114] After that, the positive electrode is made into a positive electrode through conventional processes such as coating, rolling, slitting, and drying, and is then wound into a battery cell with the negative electrode, separator, and electrolyte products conventionally used in the art.

[0115] Example 2

[0116] A positive electrode slurry is prepared using raw materials of lithium iron phosphate, a conductive agent and a glue solution. The difference from Example 1 is that the organic solvent acetone in the preparation process of the flexibilizer is replaced with methanol.

[0117] Example 3

[0118] A positive electrode slurry is prepared from raw materials of lithium iron phosphate, a conductive agent and a glue solution. The difference from Example 1 is that the conductive agent a is replaced by acetylene black instead of SP.

[0119] Comparative Example 1

[0120] The difference from Example 1 is that no nitrile polymer and flexibilizer are added to the raw materials for preparing the glue solution, and the rest is the same as Example 1.

[0121] Comparative Example 2

[0122] The difference from Example 1 is that no nitrile polymer is added to the raw materials for preparing the glue solution, and the rest is the same as Example 1.

[0123] Comparative Example 3

[0124] The difference from Example 1 is that no flexibilizer is added to the raw materials for preparing the glue solution, and the rest is the same as Example 1.

[0125] Comparative Example 4

[0126] Different from Example 1, no type B conductive agent is added to the conductive agent of the raw material for preparing the positive electrode slurry, but the total amount of conductive agent added is the same as that in Example 1, and the ratio of type A conductive agent to type C conductive agent is the same as that in Example 1.

[0127] Comparative Example 5

[0128] Different from Example 1, no type A conductive agent is added to the conductive agent of the raw material for preparing the positive electrode slurry, but the total amount of conductive agent added is the same as that in Example 1, and the ratio of type B conductive agent to type C conductive agent is the same as that in Example 1.

[0129] Comparative Example 6

[0130] Different from Example 1, no type C conductive agent is added to the conductive agent of the raw material for preparing the positive electrode slurry, but the total amount of conductive agent added is the same as that in Example 1, and the ratio of type A conductive agent to type B conductive agent is the same as that in Example 1.

[0131] Comparative Example 7

[0132] Different from Example 1, dodecyl methacrylate was not added during the preparation of the nitrile polymer.

[0133] Comparative Example 8

[0134] Different from Example 1, during the preparation of the flexibilizer, phosphorus pentoxide is not added for phosphide treatment in step N2, and polyoxyethylene ether glycol is obtained.

[0135] Performance Testing

[0136] Comparison of light transmittance of pole piece roll pressing:

[0137] Fold the electrode in half, roll it back and forth three times with a small roller, and observe the light transmittance of the folded part. The light transmittance is used to characterize the flexibility of the electrode. After the electrode is folded in half and rolled back and forth with a small roller, the lower the light transmittance, the less damaged the electrode is, and the better the flexibility is; conversely, the higher the light transmittance, the more damaged the electrode is. The results are as follows: Figure 1 shown.

[0138] Figure 1The white dots in the figure represent the light spots that pass through. The more obvious the light spots are, the higher the light transmittance is and the worse the flexibility is. Figure 1 It can be seen that the pole piece of Example 1 has the best flexibility, while the pole piece of the comparative example without the addition of nitrile polymer and flexibilizer has obvious light transmittance and poor flexibility. The nitrile polymer does not contain dodecyl methacrylate monomer, which causes the nitrile polymer itself to become hard, which also affects the flexibility of the pole piece.

[0139] Comparison of pole piece compaction density:

[0140] The surface density is uniformly 400mg / 1540.25mm 2 , adjust the parameters of the roller pressing equipment to be consistent, and the fragment is the upper limit of compaction.

[0141] Coated film resistor:

[0142] Use the resistance meter-four-probe method to test the double-sided coated electrode and read the device parameters.

[0143] The test method for adhesion (also known as peeling force) is as follows: a 20mm×200mm separator and a 20mm×100mm battery positive electrode are pressed together at 80°C and 1MPa for 60s. The obtained sample electrode is placed in a fixture and peeled at 300mm / min. The peeling strength is recorded and the average value is taken after repeating 5 times.

[0144] The results are shown in Table 1.

[0145] Table 1

[0146]

[0147] In Table 1, the roll-pressed light transmittance gradually increases from B to D (if it is A, it means it is completely opaque), and the corresponding flexibility gradually deteriorates.

[0148] According to the rolling transmittance, it can be seen from Table 1 that the electrode flexibility of Examples 1-3 of Class B is the best, and the comparative examples 1-8 samples of Class C and D perform poorly in rolling transmittance, which will affect the overall quality and uniformity of the electrode.

[0149] As for the compaction density of the pole piece, it can be seen from Table 1 that the compaction density of Examples 1-3 is 2.58-2.6 g / cm 3 , relatively high.

[0150] As for the resistance of the coated film, it can be seen from Table 1 that the resistance of Examples 1-3 is 0.8Ω, while the resistance of Comparative Examples 4-6 is relatively high, namely 3.9Ω, 2.8Ω and 3Ω, respectively, and the conductivity is poor.

[0151] From Table 1, it can be seen that the bonding force of Examples 1-3 is 260-267 gf, indicating that the bonding force is relatively strong. The bonding force of the comparative example is relatively low, which may easily cause the electrode material to fall off or peel off in actual use.

[0152] It can be seen that the electrode of the embodiment of the present invention shows good overall performance, especially in terms of electrode compaction density and electrode bonding force, which shows that it is excellent in terms of electrode compaction and bonding performance. The roll press light transmittance has little effect on the embodiment, indicating that its slurry formula and processing process are well optimized.

[0153] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A positive electrode slurry, characterized in that: The preparation raw materials include lithium iron phosphate, conductive agent and glue. The preparation raw materials of the glue include nitrile polymer, flexibility agent and PVDF. The flexibility agent has a polyether main chain with alkane segments on the main chain. The main chain contains ester groups and phosphate groups.

2. The positive electrode slurry according to claim 1, characterized in that The conductive agent is a mixture of a first conductive agent, a second conductive agent and a third conductive agent, the first conductive agent includes carbon black, the second conductive agent includes at least one of carbon nanotubes and carbon fibers, and the third conductive agent includes graphene nanosheets.

3. The positive electrode slurry according to claim 2, characterized in that The mass ratio of the first conductive agent, the second conductive agent and the third conductive agent is 1:0.3-0.8:0.4-0.

7.

4. The positive electrode slurry according to any one of claims 1 to 3, characterized in that: In terms of mass percentage, the amount of lithium iron phosphate added to the positive electrode slurry is 92% to 96%; and / or, in terms of mass percentage, the amount of the conductive agent added to the positive electrode slurry is 0.8% to 2.2%; and / or, in terms of mass percentage, the amount of the glue added to the positive electrode slurry is 1.0% to 1.8%.

5. The positive electrode slurry according to any one of claims 1 to 3, characterized in that: The preparation method of the nitrile polymer comprises the following steps: (1) introducing nitrogen into the solvent to remove oxygen, and then adding n-butyronitrile, carboxylic acid, acrylate and dodecyl methacrylate monomers; (2) adding an initiator and heating the reaction until the solid precipitate disappears; (3) dialyzing the product obtained in step (2) with deionized water to remove impurity ions in the solution, freezing and solidifying the product, and then freeze-drying the product in a vacuum manner to obtain the nitrile polymer.

6. The positive electrode slurry according to any one of claims 1 to 3, characterized in that: The preparation method of the flexibilizer comprises the following steps: a. Mixing ethylene glycol with sodium hydroxide to obtain a mixed solution, heating the mixed solution under a protective atmosphere, adding ethylene oxide, and keeping the mixture warm to obtain polyoxyethylene ether glycol; b. Add the polyoxyethylene glycol and n-propanol to a preheated reactor, add phosphorus pentoxide, keep warm for reaction, and cool with water to obtain the flexibilizer.

7. The positive electrode slurry according to any one of claims 1 to 3, characterized in that: The preparation method of the adhesive solution comprises the following steps: adding the nitrile polymer and the flexibilizer into a solvent, stirring, and then adding the PVDF to obtain the adhesive solution.

8. A method for preparing the positive electrode slurry according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: adding part of the conductive agent, part of the lithium iron phosphate and part of the glue to perform first stirring and mixing; S2: adding the remaining conductive agent and the remaining lithium iron phosphate, adding a solvent to adjust the solid content, and stirring and mixing for the second time; S3: adding the remaining glue solution and stirring and mixing for the third time to obtain the positive electrode slurry.

9. A thick lithium iron phosphate electrode, characterized in that: The invention comprises a current collector and a coating arranged on at least one side of the current collector, wherein the coating is prepared from the positive electrode slurry according to any one of claims 1 to 7.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium iron phosphate thick electrode as claimed in claim 9.

Citation Information

Patent Citations

  • Binder for a secondary battery having superior adhesive force

    CN102770995A

  • Positive electrode for secondary cell, method for manufacturing positive electrode secondary cell, and secondary cell

    CN106463730A

  • Binder for nonaqueous secondary battery electrodes, slurry for nonaqueous secondary battery electrodes, electrode for nonaqueous secondary batteries, and nonaqueous secondary battery

    CN108701833A

  • Lithium ion battery, cathode slurry, cathode plate and preparation method thereof

    CN111816871A

  • Lithium ion battery, preparation method thereof, positive pole piece and power utilization device

    CN118693331A

Cited By

  • Dispersing and softening agent for positive electrode of lithium iron phosphate battery, preparation method of dispersing and softening agent, positive electrode slurry of lithium iron phosphate battery and positive electrode piece prepared from positive electrode slurry

    CN122060108A